Press the button: online/offline mobile applications in an agricultural context - Bartling, Mona; Sotelo, Steven; Eitzinger, Anton; Atzmanstorfer, Karl (Osterreichische Akademie der Wissenschaften, Verlag, 2016)
In many developing countries, smartphone and internet usage has become a revolution for the population and has opened up many possibilities to use new services for communication purposes. For researchers and development organizations, it is now possible to engage more directly with beneficiaries during the implementation phase of a project. However, many regions still face the problem of a non-existent or unreliable internet connection, which is why mobile applications have to be able to work offline as well as online. In order to achieve this, the new OGC standard Geopackage was used to create an offline mobile application. Geopackage can be integrated with a native Android mobile application and is especially useful for connecting with different GIS tools, since it is interoperable with various important platforms.